A queer-theoretical approach to community health psychology. (January 2014) - Nic Giolla Easpaig, Bróna R; Fryer, David M; Linn, Seònaid E; Humphrey, Rhianna H
Queer-theoretical resources offer ways of productively rethinking how central concepts such as 'person-context', 'identity' and 'difference' may be understood for community health psychologists. This would require going beyond consideration of the problems with which queer theory is popularly associated to cautiously engage with the aspects of this work relevant to the promotion of collective practice and engaging with processes of marginalisation. In this article, we will draw upon and illustrate the queer-theoretical concepts of 'performativity' and 'cultural intelligibility' before moving towards a preliminary mapping of what a queer-informed approach to community health psychology might involve.